3. 2(x + 4) = 4x + 3 - 2x + 5
2 answers:
The answer is x=3 I am pretty sure
Answer:
0 = 0
Step-by-step explanation:
2(x+4) = 4x + 3 - 2x + 5
Distribute
2 ( x + 4 ) = 4x + 3 - 2x + 5
2x + 8 = 4x + 3 - 2x + 5
Add the numbers
2x + 8 = 4x + 3 - 2x + 5
2x + 8 = 4x + 8 - 2x
Combine like trems
2x + 8 = 4x + 8 - 2x
2x + 8 = 2x + 8
Subtract 8 from both sides of the equation
2x + 8 = 2x + 8
2x + 8 - 8 = 2x + 8 - 8
Simplify
Subtract the numbers
2x = 2x
Subtract 2x from both sides of the equation
2x = 2x
2x - 2x = 2x - 2x
Simplify
Combine like terms
0=0
Result
0 = 0
The input is identity : it is true for all values .
You might be interested in
Just plug in a = 5, y = -3 in that! 2a + ay = 2(5) + 5(-3) = 10 -15 = -5 thats it!
Answer:
It's undefined
Step-by-step explanation:
That symbol is undefined
1/5 of 20 is 4. 2/5 of 20 is 8. Therefore, Ron used 8 apples to make his pies.
Answer: $26.32 step-by-step explanation: it originally was $40.00 she has a coupon for 30% 30% of 40.00 is 12 40 • 0.30 = 12 40 - 12 $28 it is now $28 after the coupon her state charges an 6% sales tax on the discounted price 6% of 28 is 1.68 28 • 0.06 = 1.68 28 - 1.68 = 26.32